Asuhan Keperawatan Pada Tn.B Dengan Efusi Pleura di Ruang Palm RSUD Dr. Soeselo Kabupaten Tegal - Moch. Faza Nadhif Zamzami; Esti Nur Janah; Wawan Hediyanto (Lembaga Pengembangan Kinerja Dosen, 2024)
Pleural effusion is an excessive accumulation of fluid in the pleural cavity, which causes disruption to the respiratory system. This condition can inhibit lung function and cause severe shortness of breath and chest pain. This study aims to apply nursing care to Mr. B who was diagnosed with pleural effusion in the hospital. B who was diagnosed with pleural effusion at RSUD dr. Soeselo, Tegal Regency. The research method used was a case study with a nursing approach consisting of assessment, nursing diagnosis, intervention, implementation, and evaluation. Based on the evaluation results, the interventions carried out such as the installation of Water Seal Drainage (WSD), oxygen administration, and health education are effective in improving the quality of breathing and reducing the symptoms experienced by patients. It is hoped that this study can be a reference in the management of patients with pleural effusion in the clinical environment.